2017
DOI: 10.1016/j.scitotenv.2017.06.100
|View full text |Cite
|
Sign up to set email alerts
|

Land use affects total dissolved nitrogen and nitrate concentrations in tropical montane streams in Kenya

Abstract: African tropical montane forests are facing fast and dynamic changes in land use. However, the impacts of these changes on stream water quality are understudied. This paper aims at assessing the effect of land use and physical catchment characteristics on stream water concentrations of dissolved organic carbon (DOC), total dissolved nitrogen (TDN), nitrate (NO-N) and dissolved organic nitrogen (DON) in the Mau Forest, the largest tropical montane forest in Kenya. We conducted five synoptic stream water samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 90 publications
1
57
3
Order By: Relevance
“…Surprisingly, our two focal farm streams had lower water column nutrient concentrations than forested streams (TN = 942–977 μg/L at farm sites vs. 372–381 μg/L at forest sites and TP = 89–183 μg/L at farm sites vs. 30–67 μg/L at forest sites). This is opposite to what is usually reported (Allan, ; Bernot et al., ; Jacobs, Breuer, Butterbach‐Bahl, Pelster, & Rufino, ; Masese et al., ). Additional sampling would be required to explain this pattern, but we speculate that one important factor could be the high biomass of emergent macrophytes at farm sites potentially increasing nutrient uptake rates (Levi et al., ; higher algal biomass at farm sites could also alter uptake rates).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Surprisingly, our two focal farm streams had lower water column nutrient concentrations than forested streams (TN = 942–977 μg/L at farm sites vs. 372–381 μg/L at forest sites and TP = 89–183 μg/L at farm sites vs. 30–67 μg/L at forest sites). This is opposite to what is usually reported (Allan, ; Bernot et al., ; Jacobs, Breuer, Butterbach‐Bahl, Pelster, & Rufino, ; Masese et al., ). Additional sampling would be required to explain this pattern, but we speculate that one important factor could be the high biomass of emergent macrophytes at farm sites potentially increasing nutrient uptake rates (Levi et al., ; higher algal biomass at farm sites could also alter uptake rates).…”
Section: Discussioncontrasting
confidence: 84%
“…is opposite to what is usually reported (Allan, 2004;Bernot et al, 2010;Jacobs, Breuer, Butterbach-Bahl, Pelster, & Rufino, 2017;Masese et al, 2017). Additional sampling would be required to explain this pattern, but we speculate that one important factor could be the high biomass of emergent macrophytes at farm sites potentially increasing nutrient uptake rates (Levi et al, 2015; higher algal biomass at farm sites could also alter uptake rates).…”
Section: Discussioncontrasting
confidence: 57%
“…In agricultural sites, nitrification was likely not N limited due to the lack of correlation between N 2 O and NH 4 -N, and this is consistent with the higher dissolved inorganic N concentrations in agricultural systems compared to forest streams, likely due to the use of the N-based fertilizer (in this case, calcium ammonium nitrate), which enters streams as runoff or leachate. Higher dissolved N values were also reported from other studies in agricultural systems, including some from the same tributaries (e.g., TDN 6.6 ± 2.60 mg/L, NO 3 -N 6.1 ± 6.1 mg/L, NH 4 -N 0.04 ± 0.03 mg/L; Masese et al, 2017), although lower values (TDN 1.80 ± 1.50 mg/L, NO 3 -N 1.62 ± 0.60 mg/L) have been reported in similar streams in the Sondu River located in the South west part of the Mau Forest Complex (Jacobs et al, 2017). These differences could be in part due to the sampling season as the latter sampling was conducted in the dry season (February-March), while both Mara studies were conducted after the short rains (November-January).…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 87%
“…Riparian forests of up to 30 m width are well-maintained and contain native tree species, such as Macaranga kilimandscharica, Polyscias kikuyuensis, Olea hochstetteri and Casearia battiscombei (Ekirapa and Shitakha, 1996). A more detailed description of land use in the study area can be found in Jacobs et al (2017). 10…”
Section: Study Areamentioning
confidence: 99%
“…January to March are the driest months. Long-term annual precipitation at 2 100 m elevation is 1 988±328 mm yr −1 (Jacobs et al, 2017). 15…”
Section: Study Areamentioning
confidence: 99%